Seismicity and 3-D body-wave velocity models across the Hengill geothermal area, SW Iceland - Obermann, Anne; Wu, Sin-Mei; Ágústsdóttir, Thorbjörg; Duran, Alejandro; Diehl, Tobias; Sánchez-Pastor, Pilar; Kristjansdóttir, Sigridur; Hjörleifsdóttir, Vala; Wiemer, Stefan; Hersir, Gylfi Páll (Frontiers in Earth Science, 2022)
We image shallow crustal structures and analyze seismicity patterns in the Hengill high-enthalpy geothermal area in SW Iceland, exploiting a temporary densification of the seismic network from 2018 to 2020. Using a subset of 6,300 high-quality manually picked P- and S-phases, we compute a minimum 1-D model for the region. The most consistent and accurate hypocenter locations are derived from a joint inversion of P and S arrival times. We demonstrate that this minimum 1-D model in combination with SeisComP detection and location algorithms can be used to produce fully-automated yet high-quality earthquake catalogs. Our analysis established that both the induced and natural seismicity in the Hengill area occurs in several distinct, spatially constrained clusters. In production and injection areas, the depth of the clusters is at about 2 km, near the bottom of the production and injection wells. These are most likely triggered by the injection and induced by the production, respectively. Outside of these clusters, the seismicity is deeper, indicating the brittle-ductile transition zone at about 4 km near the center of the Hengill volcanic area and 7 km in the southernmost region. A spatial analysis of b-values shows slightly increased values in areas with numerous injection wells and slightly decreased values in production areas. Three-dimensional crustal seismic imaging shows SE-NW trending fast velocities that extend, at 1-3 km depth between the extinct Grensdalur volcanic center and the presently active Hengill volcanic center. The fastest velocities coincide with a gravity high, traces of geothermal surface manifestations and an aero-magnetic low, probably reflecting dense solidified magmatic intrusion(s). All these anomalies are caused by high temperature at some point in the geological history of the area and are most likely due to migration of the crustal accretion and volcanic activity between the two volcanic centers. Below-average VP/VS ratios at similar depth, coincide with the main production field, likely caused by the extensive fluid extraction, which lowers the pore-pressure and consequently increases the steam dominated zone. Most of the earthquakes are at the boundary of the high and low Vp/Vs anomalies, which might indicate a region of good permeability.